Self Concept Mahasiswa UIN Sumatera Utara Medan pada Mata Kuliah Persamaan Diferensial Elementer - Afri, Lisa Dwi; Reflina (Lattice Journal : Journal of Mathematics Education and Applied, 2024)
A positive self concept can provide a strong foundation for students to face academic and social challenges, enhance self motivation, and influence their academic achievements. This research focuses on the affective aspect of students, namely self-concept, which has so far received little attention. The objective of this study is to describe the self concept of students in the Elementary Differential Equations course. The population of this study comprises students enrolled in the 2021 batch of the Elementary Differential Equations course, and a sample of 99 individuals was selected using the Slovin's rule. This research used a quantitative descriptive research method. Data were collected through self-concept questionnaires and interviews. The data were analyzed using descriptive statistics. The results of this study are as follows: (1) The average self concept score of students is 67.3253 out of the ideal score of 96. (2) There are 23 students who have a high self concept with a percentage of 23.3%, 72 students have a moderate self concept with a percentage of 72.7%, and 4 students have a low self-concept with a percentage of 4%. (3) Based on the self concept indicators, the highest average score was obtained in the indicator "having a sense of responsibility in the Elementary Differential Equations course" with a score of 3.3198 out of the ideal score of 4, while the lowest average score was in the indicator "receiving attention from friends or instructors in the Elementary Differential Equations course" with an average score of 2.040 out of the ideal score of 4.   Self concept yang positif dapat memberikan dasar yang kuat bagi mahasiswa dalam menghadapi tantangan akademik dan sosial, meningkatkan motivasi diri, dan mempengaruhi prestasi akademik mereka. Penelitian ini fokus kepada aspek afektif mahasiswa yaitu self concept yang selama ini masih kurang diperhatikan. Tujuan penelitian ini ialah untuk mendeskripsikan self concept mahasiswa pada mata kuliah Persamaan Diferensial Elementer. Populasi pada penelitian ini adalah mahasiswa yang mengikuti mata kuliah Persamaan Diferensial Elementer angkatan 2021, sampel diambil dengan aturan Slovin sebanyak 99 orang. Penelitian ini menggunakan metode penelitian deskriptif kuantitatif. Teknik pengumpulan data dengan mengumpulkan angket self concept dan wawancara. Data dianalisis dengan statistik deskriptif. Hasil pada penelitian ini diperoleh yakni (1) Rata-rata self concept mahasiswa yaitu 67,3253 dari skor ideal 96. (2) Terdapat 23 mahasiswa yang memperoleh self concept kategori tinggi dengan persentase 23,3%, sebanyak 72 mahasiswa memperoleh self concept kategori sedang dengan persentase 72,7%, dan 4 mahasiswa yang memperoleh self concept kategori rendah dengan persentase 4%. (3) Berdasarkan indikator self concept, pada indikator memiliki rasa tanggung jawab dalam mata kuliah Persamaan Diferensial Elementer diperoleh dengan rata-rata tertinggi yaitu skor 3,3198 dari skor ideal yaitu 4, dan rata-rata skor terendah pada indikator memperoleh perhatian dari teman atau dosen pada mata kuliah Persamaan Diferensial Elementer dengan rata-rata skor 2,040 dari skor ideal yaitu 4.